2019
DOI: 10.1080/17517575.2019.1706192
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ERP utilisation experience and segmental reporting on corporate performance in the UK context

Abstract: By adopting the Decision-Usefulness theory, this study investigates separately and jointly the impact of utilising Enterprise Resources Planning system (ERPs) and the information disclosure of Segmental Reporting (SR), following the implementation of IFRS-8, on Corporate Performance (CP) in the UK context. The research was drawn on the Financial-Times-Stock-Exchange (FTSE)-100 over the period 2013-2017 using textual analysis and Compustat, after accounting for endogeneity problems. The authors find generally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
(125 reference statements)
3
4
0
Order By: Relevance
“…These results are in line with those of previous studies that report a positive and significant relationship amongst these variables (Al-Dhaafri and Alosani, 2020;Abu-Rumman et al, 2021;Abdullah and Tari, 2012;Ahmed and Idris, 2020;Al-Dhaafri and Alosani, 2020;Chopra and Mendl, 2013;Chong and Rundun, 2004;Faisal et al, 2011;Hassan and Kerr, 2003;Gunday et al, 2011;Hendricks and Singhal, 2001;Joiner, 2007;Kumar et al, 2009;Miyagawa and Yoshida, 2010;Thai and Jie, 2018). Similarly, ERP was found to have positive and significant effect on organizational excellence and performance (β 5 0.096, t 5 2.020, p < 0.05), (β 5 0.277, t 5 2.340, p < 0.05) which is consistent with finding of Al-Dhaafri et al (2016a, b), Al-Dhaafri and Al-Swidi (2014), Bendoly and Kaefer (2004), Elsayed et al (2021), Maiga et al (2014), Park et al (2007, Poston and Grabski (2001) and Sislian and Jaegler (2020).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are in line with those of previous studies that report a positive and significant relationship amongst these variables (Al-Dhaafri and Alosani, 2020;Abu-Rumman et al, 2021;Abdullah and Tari, 2012;Ahmed and Idris, 2020;Al-Dhaafri and Alosani, 2020;Chopra and Mendl, 2013;Chong and Rundun, 2004;Faisal et al, 2011;Hassan and Kerr, 2003;Gunday et al, 2011;Hendricks and Singhal, 2001;Joiner, 2007;Kumar et al, 2009;Miyagawa and Yoshida, 2010;Thai and Jie, 2018). Similarly, ERP was found to have positive and significant effect on organizational excellence and performance (β 5 0.096, t 5 2.020, p < 0.05), (β 5 0.277, t 5 2.340, p < 0.05) which is consistent with finding of Al-Dhaafri et al (2016a, b), Al-Dhaafri and Al-Swidi (2014), Bendoly and Kaefer (2004), Elsayed et al (2021), Maiga et al (2014), Park et al (2007, Poston and Grabski (2001) and Sislian and Jaegler (2020).…”
Section: Discussionsupporting
confidence: 87%
“…Many previous studies found a strong effect of ERP on organizational performance (Al-Dhaafri et al, 2016a, b;Elsayed et al, 2021;Maiga et al, 2014;Sislian and Jaegler, 2020); however, this conclusion still has many contradictions, which encourages us to examine this relationship based on the following hypotheses:…”
Section: Enterprise Resource Planningmentioning
confidence: 98%
“…These results are consistent with previous studies that found a positive and significant relationship between these variables (Abu-Rumman et al , 2021; Abdullah and Tari, 2012; Ahmed and Idris, 2020; Al-Dhaafri and Alosani, 2020; Chopra and Mendl, 2013; Chong and Rundun, 2004; Faisal et al , 2011; Hassan and Kerr, 2003). Similarly, ERP was found to have a positive and significant impact on organizational performance ( β = 0.260, t = 2.249, p < 0.05), which is consistent with the results of Al-Dhaafri et al (2016a, b), Al-Dhaafri and Al-Swidi (2014), Bendoly and Kaefer (2004), Elsayed et al (2021), Maiga et al (2014), Park et al . (2007), Poston and Grabski (2001) and Sislian and Jaegler (2020).…”
Section: Discussionsupporting
confidence: 88%
“…Many previous studies discovered a clear impact of ERP on organizational performance (Al-Dhaafri et al, 2016a, b;Elsayed et al, 2021;Maiga et al, 2014;Sislian and Jaegler, 2020), but this conclusion still has many inconsistencies, prompting us to investigate this relationship based on the following hypotheses:…”
Section: Enterprise Resource Planningmentioning
confidence: 99%
“…The second research stream indicates positive outcomes to ERP systems (AlMuhayfith & Shaiti, 2020; Anderson et al, 2011;Bialas et al, 2023a;Elsayed et al, 2021;Galy & Sauceda, 2014;Hendricks et al, 2007;Hitt et al, 2002;Hunton et al, 2003;Kallunki et al, 2011;Madapusia & D'Souza, 2012;Matolcsy et al, 2005;Nicolaou et al, 2003;Nicolaou, 2004;Ruivo et al, 2020;Santoso et al, 2022;Tarigan et al, 2021). For instance, Ince et al (2013) found positive effects of ERP systems on firm performance and competitive advantage.…”
Section: Introductionmentioning
confidence: 99%